ANALYSIS OF QUALITY MANAGEMENT IMPLEMENTATION OF OPERATIONAL PERFORMANCE THROUGH A CULTURE OF QUALITY AND PRODUCTIVE BEHAVIOR OF EMPLOYEES AT PT. SANTOSA UTAMA LESTARI UNIT CORN DRIER KETAPANG SOUTH LAMPUNG - Silvia Damayanti; Ardansyah (ZILLZELL MEDIA PRIMA, 2024)
In the current era of globalization, companies or industries are encouraged to make changes in a very fast and competitive business environment. The company's success is supported by effective and efficient quality management. Research problems that can be formulated are not having good quality management, operational performance that has not met targets, not having a good quality culture, and good employee productive behavior. This study aims to analyze the implementation of quality management on operational performance through quality culture and productive behavior of employees. The research method used is a quantitative approach using Structural Equation Modelling Partial Least Square (SEM – PLS) analysis using the object of research at PT. Santosa Utama Lestari Unit Corn Drier Ketapang South Lampung. Quality management has a negative influence on operational performance. Quality management positively influences quality culture. Quality management has a positive effect on productive behavior. Quality culture negatively affects operational performance. Quality management variables and quality culture variables as mediating variables negatively affect operational performance variables. Quality management variables and productive behavior variables as mediating variables negatively affect operational performance variables.